Investigating relationship between gold price and crude oil price using interval data with copula based GARCH - Teerawut Teetranont (2018)
© Springer International Publishing AG 2018. This study investigates and compares the performance of center method, equal weighted convex combination and unequal-weighted convex combination methods through various GARCH and copula-based approaches for the analysis of relationship between gold and crude oil prices using interval data in Comex and Nymex tradings. The results of this study confirm that unequal-weighted convex combination method improves the estimation and it tends to perform better than both the center method and its equal-weighted variant. In addition, the marginal from the best fit GARCH model is used to measure dependence via copula function in the form of Student-t copula as selected according to the lowest AIC among all candidates. Finally, we can conclude that there exists the dependence between Comex and Nymex not only in the normal event, but also in the extreme event.